The effectiveness of instructional module in the study of chemical equilibrium - Ulep, Roque Antonio (Animo Repository, 1989)
The study focuses on the effectiveness of a self-instructional module in the study of Chemical Equilibrium which was a two-phase investigation: development (phase 1) and evaluation (phase 2). The development phase included six learning modules used in the study, each with a set of learning objectives, learning programs and review problems. The evaluation phase involved the experimental try-out at the Mariano Marcos State University using college engineering students taking up general chemistry. 2. Ninety nine students were involved in the study, 27 in the experimental group, 37 in control group 1 and 35 in the control group. 2. The pretest-posttest control group experimental design was used in the study and the results were analyzed employing the mean, mean difference and ANCOVA to determine if the adjusted mean of the experimental group is not significantly different from the adjusted means of the two control groups with pretest as covariate. The design of the module was evaluated by the experimental group and by seven chemistry instructors using a questionnaire that considered such points to determine usefulness, clarity, content and format of the module. After the experimental evaluation, the analysis of results revealed that both the teachers' and students' evaluators showed favorable responses as to the usefulness, clarity, content and format of the module developed. Moreover, the researcher observed during the experiment that the students treated to the modular approach acquired more positive attitudes towards learning and show favorable interest on the use of self-instructional material because they are self motivated. This further requires less assistance during the learning process. As to the effectiveness of the module, the experimental group is apparently higher than the two control groups as far as the mean of the gain score is concerned. This is evidenced by the greater average gain obtained by the experimental group. The application of the statistical test (ANCOVA) resulted the acceptance of the null hypothesis which shows that there is no significant difference between the means of the posttest scores of the experimental group and two control groups. The approach used (problem solving approach) is effective to both types of treatment (modular and traditional) and the achievements and improvements of the students among the three groups in the experiment is attributed by the approach used in the study of Chemical Equilibrium. This is evidenced by the result of the statistical test (t-test for independent sample) which shows that there is no significant difference between the means of their grades in both Mathematics and Chemistry. This finding further showed that the improvement of the students using the modular approach is not significantly different from the achievement of the students using the traditional approach. In short, the use of modular approach is as effective as the traditional method and can be used as a substitute for delivering concepts and principles of Chemical Equilibrium.